Mediating role of neuroticism in the association between loneliness and cognitive function among community‐dwelling older adults. (26th June 2018) - Foong, Hui Foh; Hamid, Tengku Aizan; Ibrahim, Rahimah; Haron, Sharifah Azizah
Abstract : Objective: The main aim of this study was to examine whether neuroticism mediates the association between loneliness and cognitive function in older adults. Methods: This study involved 2322 representative community residents aged 60–92 years in Peninsular Malaysia. Cognition was measured by Mini‐Mental State Examination (MMSE), loneliness was assessed by three‐item loneliness scale, and neuroticism was assessed by the Short‐Form Revised Eysenck Personality Questionnaire. Hierarchical multiple linear regression and Sobel tests were used for mediation analyses. Results: Both loneliness (β = −0.04, P = 0.03) and neuroticism (β = −0.07, P < 0.001) were negatively and significantly associated with cognitive function, and most importantly, neuroticism mediated the association between loneliness and cognition (from β = −0.04, P = 0.03 to β = −0.03, P = 0.10). Conclusion: Neuroticism may be the potential mechanism underlying the relationship between loneliness and cognitive function in older persons.